Women's Representation in Three-tier Parliamentary Elections in Nepal 2017-2022 (The Journal of Knowledge and Innovation, 2024)
The gender quota is a significant strategy to enhance the global representation of women in legislative bodies. Nepalese Constitution 2015 implemented a 33 percent women's quota through a mixed electoral system, ensuring their inclusion. The study analyzes women's representation in Nepal's three-tier parliament elections from 2017 to 2022, using a quantitative, descriptive research design with data from the Election Commission Nepal to identify patterns and trends in women's political participation. It evaluates the constitutional provisions for gender inclusivity through the theoretical frameworks of liberalism and multiculturalism. Nepal ended a 250-year monarchy in 2008 and smoothly transitioned into a federal democratic republic. With the adoption of the new federal Constitution in 2015, Nepal completed two rounds of elections in 2017 and 2022 at all three levels. All three levels of Parliament are inclusive, and the federal and provincial levels achieved one-third of women's participation in both elections. Moreover, the local level had a women's share of 41 percent in 2017 and 41.2 percent in 2022. The overall women representation was 40.8 percent in 2017 and 41.1 percent in 2022. However, reservation quotas and proportional systems only fulfilled the women's representation. There needs to be more representation of women in the first past the post-election. Women need a frontline leadership position due to a lack of capacity or barriers in political parties, economic deprivation, and lack of networking of women. Even though the country has become a federal democratic republic, women are still being affected by the patriarchal mindset. Implementing a women's quota into the direct electoral system is essential to promote women's leadership. Female seats at any level should not be reduced, even in candidate selection in the interparty coalition arrangement. The quota for women in Parliament should be raised to fifty percent to ensure their fair representation.